2019
DOI: 10.1177/1687814019884420
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of strength characteristics of carbon fiber–reinforced microbial solidified sand

Abstract: Microbial solidified sand effectively enhances the strength of the soil, but it will cause brittle failure. In order to reduce the impact of microbial solidification sand brittleness, an improved method for adding carbon fiber to microbial solidified sand is proposed. The qualitative analysis was based on unconfined compressive strength test, calcium carbonate content determination, and penetration test. The results show that the addition of fiber in the microbial solidified sand can significantly increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The strength gain turned out to be less when the fiber addition became more than 1%, but the samples’ ductility was enhanced significantly. Since bio-cemented sand is typically a brittle material, fiber addition provides an essential improvement for bio-cemented sand samples on strength and stress–strain behaviors [ 30 ]. It is worth noting that there is a delicate balance between strengthening and softening in terms of peak strength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strength gain turned out to be less when the fiber addition became more than 1%, but the samples’ ductility was enhanced significantly. Since bio-cemented sand is typically a brittle material, fiber addition provides an essential improvement for bio-cemented sand samples on strength and stress–strain behaviors [ 30 ]. It is worth noting that there is a delicate balance between strengthening and softening in terms of peak strength.…”
Section: Resultsmentioning
confidence: 99%
“…fiber addition provides an essential improvement for bio-cemented sand samples on strength and stress-strain behaviors [30]. It is worth noting that there is a delicate balance between strengthening and softening in terms of peak strength.…”
Section: Unconfined Compressive Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies showed that using fibrous materials increased bacterial interactions with the cementation solution and facilitated uniform CaCO 3 precipitation within the sand pores in MICP-treated soil [ 8 ]. Several studies have also revealed that the addition of fiber materials can substantially increase the engineering properties of MICP-treated soil (for example the shear strength, ductility, brittleness behavior, internal friction, and rigidity) [ 9 ]. However, to address these challenges, most of these previous studies focused on using synthetic-polymer-based fiber materials, such as non-woven geotextile fiber, steel fiber, polypropylene fiber, glass fiber, and carbon fiber, which are associated with relatively high costs, health concerns, and environmental hazards [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…e brittle failure was prevented because the solidified sand would not lose strength immediately after the damage [23,24]. Most of the previous research mainly used polypropylene fiber as the reinforcement for the microbial solidified sand.…”
Section: Introductionmentioning
confidence: 99%